Immunochemical properties of Vibrio cholerae LPS - Bukovský, M; Ciznár, I (Folia microbiologica, 1993)
Immunochemical analysis of LPS isolated from Vibrio cholerae O1 and non O1 showed that this macromolecular complex shares common antigenic epitopes in the sugar moiety. The epitopes can be detected after mild alkaline hydrolysis of LPS in vitro. Membrane-associating activity of both O1 and non O1 LPS did not indicate any differences of the species.
Keywords: Sheep; Antigens, Bacterial; techniky in vitro; Epitopes; Immunoelectrophoresis; druhová specificita; lipopolysacharidy; imunoelektroforéza; Precipitin Tests; Hemolysis; Lipopolysaccharides; antigeny bakteriální; zvířata; Immunochemistry; Vibrio cholerae; precipitinové testy; Immunodiffusion; Species Specificity; In Vitro Techniques; imunodifuze; imunochemie; Animals; epitopy; hemolýza; ovce